STUDY ON TWO-SCALE UNIFIED CONSTITUTIVE MODEL AND DAMPING MECHANISM OF RUBBER CONVEYOR BELT WITH STEEL WIRE ROPE CORE - LI JianGang; FENG JinPing; WANG Xin; LIU SiYuan; GAO ZhongJie; WU JianJun (Jixie qiangdu)
Constitutive analysis of steel wire rope conveyor belt is a key problem for conveyor belt design optimization and energy conservation. Maxwell model and Burgers model based on viscoelastic theory and transient dynamics were constructed. Considering the fretting friction damping between steel wires and the mutual damping between steel wire rope and conveyor belt， a mixed constitutive model was constructed. Under the condition of 0~30 ℃， the relationship between the parameters of the constitutive model was established， the simulation curve was fitted and solved by Matlab， and the accuracy of the mixed constitutive model was verified by taking 40 ℃ as the control group. The verification results show that the maximum error between the conveyor belt represented by this constitutive model and the experiment is 5.88%， demonstrating that this constitutive model can better characterize the rubber conveyor belt with steel wire rope core. The universality of this model is verified by the method of simulation and prediction. This study provides a theoretical basis for the structural optimization and energy-saving analysis of conveyor belt.